Synthesis of novel enantiopure fluorinated building blocks from acyclic chiral allylsilanes. - Tredwell, M; Tenza, K; Pacheco, M; Gouverneur, V (2005)
[reaction: see text] Homochiral beta-fluorinated gamma,delta-unsaturated carboxylic acids with an allylic fluorinated stereogenic center are available from the corresponding enantiopure allylsilanes. The key step for introduction of the fluorine substituent is an electrophilic fluorodesilylation reaction carried out in the presence of Selectfluor. Reduction of the resulting beta-fluorinated pentenoic acid into the corresponding fluorinated alcohol was also performed leading to the formation of an enantiopure second-generation fluorinated building block.